Galapagos: On the Logic and Limitations of Generic Solvers - Rutten, David (Architectural design, 2013)
A graduate in architecture and urbanism from TU Delft, David Rutten works with software company Robert McNeel & Associates (RMN). The developer of Grasshopper®, he was recently awarded the ACADIA 2012 award for innovative research. The Galapagos plug‐in, which Rutten has developed for Grasshopper®, implements two generic solvers (one using a genetic algorithm and one using a simulated annealing algorithm). A generic solver will find a solution to a problem that can be expressed in a mathematical way; however, as he explains here, while these solutions may not be exact, they will be very good.